(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This study is an attempt to determine the blend of fancy and fact in Sagrika Ghose’s novel Blind Faith. This novel is fully ripened with occurrences which are fanciful and fictional and yet the novel reflects the realities of life. This novel is ripe with tragedy and pain. Every character has its own story. Every character appears with one’s own faith. At some part of this novel fancy is used rather like a collective consciousness. In this age of reasoning and logic such activities would be rubbished as mere concoctions of a fanciful mind. Questions may be raised by a layman regarding the myths that the novel presents. How can a person like Vik alias Karna perform such kinds of activities at the same time? Is the writer experimenting with magic realism or rebuffing it? Or is she probing the psychological maladies to justify human behavior, which is otherwise understood as fanciful?